2011
DOI: 10.1002/ijc.26470
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus in women with invasive cervical carcinoma by HIV status in Kenya and South Africa

Abstract: Data on the prevalence of human papillomavirus (HPV) types in cervical carcinoma in women with HIV are scarce but are essential to elucidate the influence of immunity on the carcinogenicity of different HPV types, and the potential impact of prophylactic HPV vaccines in populations with high HIV prevalence. We conducted a multicentre case-case study in Kenya and South Africa. During 2007-2009, frozen tissue biopsies from women with cervical carcinoma were tested for HPV DNA using GP51/61-PCR assay. One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
5
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 27 publications
11
66
5
8
Order By: Relevance
“…In China, HPV16/18 was the predominant typo, followed by 58, 31, and 52 (Bao et al, 2008). These data showed that HPV distribute with region and nationalistic difference (Velicer et al, 2009;De Vuyst et al, 2012). Guzalinuer genotyped the HPV in 100 cervical cancer cases in west Xinjiang province (Guzalinuer et al, 2007) .The result shows that HPV 16, 18 and 68 were the most important HPV type, there exist large different with our study, but our study is population-based and more representative for Uyghur HPV genotype.…”
Section: Discussionmentioning
confidence: 78%
“…In China, HPV16/18 was the predominant typo, followed by 58, 31, and 52 (Bao et al, 2008). These data showed that HPV distribute with region and nationalistic difference (Velicer et al, 2009;De Vuyst et al, 2012). Guzalinuer genotyped the HPV in 100 cervical cancer cases in west Xinjiang province (Guzalinuer et al, 2007) .The result shows that HPV 16, 18 and 68 were the most important HPV type, there exist large different with our study, but our study is population-based and more representative for Uyghur HPV genotype.…”
Section: Discussionmentioning
confidence: 78%
“…The IARC has coordinated cervical cancer case series, cervical cancer case-control studies, and population-based HPV prevalence surveys in a large number of countries around the world (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35); also as-yet-unpublished studies from Fiji and Bhutan). The collection of samples has spanned a period of over 20 years from 1989 until 2012 and predates the introduction of HPV vaccines.…”
Section: Methodsmentioning
confidence: 99%
“…Levin et al 31 conducted a double-blinded placebo-controlled safety and immunogenicity trial that enrolled and randomised 126 HIV-infected boys and girls aged [7][8][9][10][11][12] Number of studies included in the final review for the current study (6) Duplicates (10) Not written in English (10) Not meeting inclusion criteria (447) Fig. 1.…”
Section: Studies In Hiv-infected Childrenmentioning
confidence: 99%